Nonhuman primates parasitic and noninfectious diseases. - VanHoosier, G L.; Whitney, Robert A. (Robert Arthur), 1935-; American College of Laboratory Animal Medicine; Washington State University. College of Veterinary Medicine; University of Washington. Health Sciences Learning Resources Center (Seattle, Wash. : G.L. VanHoosier, Jr., distributed by Health Sciences Learning Resources Center, University of Washington, 1978)
Discusses protozoan and metazoan parasites, including signs, treatment and life cycles. Also discusses noninfectious diseases of nonhuman primates including vitamin deficiency.
Includes bibliographical references.
Preparer, Robert A. Whitney, Jr.
Keywords: Primates -- Diseases